Final analysis of the phase 1b Chemotherapy and Venetoclax in Elderly Acute Myeloid Leukemia Trial (CAVEAT) - Chong Chyn Chua; Sun Loo; Chun Yew Fong; Stephen B. Ting; Ing Soo Tiong; Shaun Fleming; Natasha S. Anstee; Adam Ivey; Michael Ashby; Tse-Chieh Teh; John Reynolds; Andrew W. Roberts; et al. (Blood Advances)
Abstract: Venetoclax plus azacitidine represents a key advance for older, unfit patients with acute myeloid leukemia (AML). The Chemotherapy and Venetoclax in Elderly AML Trial (CAVEAT) was first to combine venetoclax with intensive chemotherapy in newly diagnosed patients aged ≥65 years. In this final analysis, 85 patients (median age, 71 years) were followed up for a median of 41.8 months. The CAVEAT induction combined cytarabine and idarubicin with 5 dose levels of venetoclax (50-600 mg) for up to 14 days. Two additional cohorts explored adjusted-dose venetoclax (50 mg and 100 mg) with posaconazole. CAVEAT induction was well tolerated, with low mortality (4%) and limited high-grade gastrointestinal toxicity (4%). Delayed hematologic recovery after consolidation was ameliorated by omitting idarubicin from postremission therapy. The overall response rate (ORR; complete response [CR] + CR with partial hematologic recovery + CR with incomplete count recovery) was 75%, with a median overall survival (OS) of 19.3 months (95% confidence interval [CI], 11.1-31.3). Among de novo AML, ORR was 88% and median OS was 33.1 months (95% CI, 19.3-54.3). Almost one-third have not relapsed, many benefiting from prolonged treatment-free remission (median, 17.9 months). CAVEAT induction was well tolerated and associated with high ORR that was durable, particularly for de novo AML. CAVEAT represents an effective time-limited treatment option for fit, older patients with AML. This trial was registered at https://www.anzctr.org.au as #ACTRN12616000445471.